2019
DOI: 10.1590/s1677-5538.ibju.2017.0681
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness evaluation of open reanastomosis for obliterative or recalcitrant anastomotic stricture after radical retropubic prostatectomy

Abstract: Purpose: To evaluate safety, efficacy and functional outcomes after open vesicourethral re - anastomosis using different approaches based on previous urinary continence. Materials and Methods: Retrospective study of patients treated from 2002 to 2017 due to vesicourethral anastomosis stricture (VUAS) post radical prostatectomy (RP) who failed endoscopic treatment with at least 3 months of follow-up. Continent and incontinent patients post RP were assigned to abdominal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Reconstructive approaches in the setting of prior radiation are notoriously difficult and most reports describe recurrence rates of 30% or higher. 17-23 The most recent data at the time of this report come from the Trauma and Reconstructive Urology Working Party of the European Association of Urology, who report a recurrence-free rate of 67% for 47 patients after a median of 44 months of follow-up. 24 We have not found that bladder neck reconstruction with the use of buccal mucosa grafts or muscle flaps offers a reliable, long-term solution in this population and do not routinely offer this, making it difficult to draw comparisons between these approaches and the use of up-front AUS placement in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstructive approaches in the setting of prior radiation are notoriously difficult and most reports describe recurrence rates of 30% or higher. 17-23 The most recent data at the time of this report come from the Trauma and Reconstructive Urology Working Party of the European Association of Urology, who report a recurrence-free rate of 67% for 47 patients after a median of 44 months of follow-up. 24 We have not found that bladder neck reconstruction with the use of buccal mucosa grafts or muscle flaps offers a reliable, long-term solution in this population and do not routinely offer this, making it difficult to draw comparisons between these approaches and the use of up-front AUS placement in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…40 Open VUAS or bladder neck reconstruction can be performed retropubically or perineally with patency rates ranging from 70-100%. [42][43][44] In patients continent of urine preoperatively who had a retropubic approach, 10% were incontinent post-operatively, while those who had a perineal reconstruction had an 83.3% incontinence rate post-operatively. 42,43 Special Circumstances 30.…”
Section: Guideline Statementsmentioning
confidence: 99%
“…[42][43][44] In patients continent of urine preoperatively who had a retropubic approach, 10% were incontinent post-operatively, while those who had a perineal reconstruction had an 83.3% incontinence rate post-operatively. 42,43 Special Circumstances 30. In men who require chronic selfcatheterization (eg, neurogenic bladder), surgeons may offer urethroplasty as a treatment option for urethral stricture causing difficulty with intermittent selfcatheterization.…”
Section: Guideline Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported definitions range between failure after one to >3 procedures. [19][20][21][22][23][24] The treatment carries an economic burden. It is estimated that in the UK, an elective bladder neck incision (BNI) procedure costs £1204-2987 in the elective setting and this cost rises threefold if it is performed in the emergency setting.…”
Section: Refractory Bnc: Definition Prevalence and Socioeconomic Impactmentioning
confidence: 99%